2022
DOI: 10.3390/met12111814
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Approach for the Intercritical Annealing of (Cr, Mo, V)-Alloyed TRIP-Assisted Steel before Austempering

Abstract: TRIP-assisted С-Si-Mn steels are usually subjected to austempering with a preliminary intercritical annealing that is targeted at the multi-phase structure with 40–60 vol.% of proeutectoid ferrite. The kinetics and the mechanism of phase-structural transformations can be impacted due to the additional alloying of TRIP-assisted steel by the strong carbide forming elements, thus necessitating an alternative approach for the selection of intercritical annealing parameters. This issue is analyzed in the present wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The dark-field observation in the cementite reflection and the corresponding SAED analysis in the inset of Figure 7d confirmed that the lamellae were cementite carbide. This observation explained the decrease in TEL to 17% compared to 22% in TMCP/AC 550 since the borderline cementite precipitates were considered a negative factor affecting steel ductility [52]. Additionally, nano-sized (Nb,V)C precipitates were found in the structure (Figure 7c) with an approximately similar size distribution as the TMCP/AC 550 structure (Figure 6b).…”
Section: Microstructure Characterizationmentioning
confidence: 85%
“…The dark-field observation in the cementite reflection and the corresponding SAED analysis in the inset of Figure 7d confirmed that the lamellae were cementite carbide. This observation explained the decrease in TEL to 17% compared to 22% in TMCP/AC 550 since the borderline cementite precipitates were considered a negative factor affecting steel ductility [52]. Additionally, nano-sized (Nb,V)C precipitates were found in the structure (Figure 7c) with an approximately similar size distribution as the TMCP/AC 550 structure (Figure 6b).…”
Section: Microstructure Characterizationmentioning
confidence: 85%
“…The combination of the CALPHAD approach and the Johnson-Mehl-Avrami-Kolmogorov model allows for the simulation of solid-phase transformations. This simulation provides an opportunity to develop heat treatment modes of steels and cast irons [25].…”
Section: Introductionmentioning
confidence: 99%
“…According to research on austempering stainless steels changes in phase behavior and development can change the bestaustempered temperature for optimal strength and flexibility. Processing methods such as inter critical annealing before austempering can alter multi-phase microstructure [22], which is like research on TRIP-assisted steel austempering. Studies here, show coating low-alloy steel in molten Bi-Ga can strengthen it and prevent rust if heat-treated right.…”
Section: Introductionmentioning
confidence: 99%